Manajemen Konferensi Mahasiswa Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung - Hidayatul Fikra; Fitriani Fitriani; Susanti Vera (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to describe conference activities specifically for students. This research uses a qualitative approach by applying the policy review method. The results and discussion of this research show that student-specific conference activities bring a conducive climate to the creation of a healthy academic culture where students are motivated to excel, intensively practice scientific article writing, strengthen foreign language skills in presenting articles at conference activities, and become productive in publications. scientific articles in the form of proceedings. This research concludes that special student conferences provide valuable experience in creating scientific publication productivity as a form of progress in higher education in Indonesia.